Characterization of nano-bio silicon carbide - Vlaskina, S.I.; Mishinova, G.N.; Shaginyan, I.L.; Smertenko, P.S.; Svechnikov, G.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2020)
Plasma-enhanced chemical vapor deposition, reactive magnetron sputtering, hotwire chemical vapor deposition, and radio frequency plasma-enhanced chemical vapor deposition were used to develop technology for the preparation of nano-bio silicon carbide coating of ceramic materials for dental applications. The effect of the bias voltage applied to the ceramic prostheses and dental crowns on the crystallization processes has been recognized. The optimal bias voltage applied to the conductive substrate was –200 V, whereas for the dielectric substrate, the bias voltage bᵢₐₛ did not affect the properties of the SiC coating. The analysis of CVCs and spectroscopic diagnostics as methods for studying the mechanism of interfacial rearrangements to investigate the SiC phase transition in nano silicon carbide coatings was used. The conductivity of the SiC coating coincided with the conductivity of the dielectric (µ₀ = 10¹²…10¹³ сm⁻¹·s⁻¹·V⁻¹). The conductive substrate had a significant effect on the properties of the coating and thus depended on the bias voltage bᵢₐₛ. The conductivity increased by three-four orders of magnitude (µ₀ = 3·10¹⁷ сm⁻¹·s⁻¹·V⁻¹), if the bias voltage bᵢₐₛ = –200 V. The increase of the bias voltage (bᵢₐₛ = –600 V) led to a decrease in the conductivity (µ₀ = 10¹¹…10¹² сm⁻¹·s⁻¹·V⁻¹). It was found that there was a double injection regime with bimolecular recombination in this structure, with the dependence = ³ᐟ² for CVCs of SiC. The luminescence spectrum of SiC coating on nondielectric ceramics (if bᵢₐₛ = – 200 V during deposition) was significantly different from the luminescence spectrum of SiC coating on dielectric ceramics. Increasing the applied voltage to the substrate bᵢₐₛ during deposition led to an increase in the fraction of hexagonal polytypes. Directions in the crystal lattice according to the photoluminescence spectra were identified by comparing the values of the width of the non-phonon parts of stacking faults and deep level spectra in the low-temperature photoluminescence with arrangements of atoms in the SiC lattice structure. The displacement of each atom participating in photoluminescence allowed us to find the correlation with the technology of SiC deposition and to develop the technology of SiC coating on the dental materials. Плазмове посилене хімічне осадження пари, реактивне магнетронне розпилення, хімічне осадження з гарячим дротом та посилене хімічне випаровування радіочастотною плазмою використовувались для розробки технології підготовки нанобіопокриття з карбіду кремнію з керамічних матеріалів для стоматологічних застосувань. Визнано вплив напруги зміщення, що застосовується до керамічних протезів та зубних коронок, на процеси кристалізації. Оптимальна напруга зміщення, яка подається на провідну підкладку, становила −200 В, тоді як для діелектричної основи напруга зміщення bᵢₐₛ не впливала на властивості покриття SiC. Використовували аналіз вольт-амперних характеристик та спектроскопічну діагностику як методи вивчення механізму міжфазних перебудов для дослідження фазового переходу SiC у нанокристалічних покриттях з карбіду кремнію. Провідність покриття SiC збіглася з провідністю на діелектрику (µn₀ = 10¹²…10¹³ cm⁻¹·s⁻¹·V⁻¹). Провідна підкладка мала значний вплив на властивості покриття, і це залежало від напруги зміщення bᵢₐₛ. Провідність зросла на три–чотири порядки величини (µn₀ = 3·10¹⁷ cm⁻¹·s⁻¹·V⁻¹), якщо напруга зміщення bᵢₐₛ = –200 В. Збільшення напруги зміщення (bᵢₐₛ = –600 В) призвело до зменшення провідності (µ₀ = 10¹¹…10¹² cm⁻¹·s⁻¹·V⁻¹). Встановлено, що в цій структурі існував режим подвійного введення з бімолекулярною рекомбінацією із залежністю I = V3/2 для вольт-амперних характеристик SiC. Спектр люмінесценції покриття SiC на недіелектричній кераміці (якщо bᵢₐₛ = –200 В під час осадження) суттєво відрізнявся від спектра люмінесценції покриття SiC на діелектричній кераміці. Збільшення прикладеної напруги до підкладки bᵢₐₛ під час осадження призвело до збільшення частки гексагональних політипів. Напрямки в кристалічній решітці за спектрами фотолюмінесценції були визначені із порівняння значень ширини нефононних частин розломів укладання та спектрів глибинного рівня в низькотемпературній фотолюмінесценції з розташуванням атомів у структурі решітки SiC. Зміщення кожного атома фотолюмінесценції, що брав участь, дозволило зробити кореляцію в технології осадження SiC та розробити технологію покриття SiC на стоматологічних матеріалах.